Study of Destruction of Organic Substances in Water Solutions by Pulsed Electrical Discharges in the Iron Granules Layer; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Lobanova G. L. Galina Leonidovna; Yurmazova T. A. Tatyana Aleksandrovna; Shiyan L. N. Lyudmila Nikolaevna; Magomadova S. O. (Discharge and Plasma-Beam Technology, 2016)
Title screen